Easing the Tourism Burden in Kawasan Kota Tua Jakarta (Jakarta's Old City Area) through Carrying Capacity Studies and Activity Mapping - Nugroho, Fajar Aditya; Silvia; Aripinur, Putra; Izzah, Shafira Nurul; Shelbina, Raisya; Wulandari, Nurmala Aulia (International Journal of Sustainable Competitiveness on Tourism, 2025)
As one of the sites that are vulnerable to damage, historical areas, especially heritage sites, need special attention in their utilization, especially for tourism. In finding a middle ground between conservation needs and tourism utilization efforts, this study presents a scientific breakthrough by combining the concept of urban heritage tourism with tourism carrying capacity. Taking a case study in the Old City Area of Jakarta and an exploratory qualitative-quantitative approach armed with a tourism carrying capacity calculation formula, this study found the fact that the actual perspective is more heavily directed towards tourism interests than conservation. This is indicated by the finding that the number of tourist visits per day exceeds the Effective Carrying Capacity (ECC). Therefore, efforts are needed to spread tourism activities to other points in the destination as in the recommended tourism activity map generated with the help of the Cadmapper software application.